IMPLEMENTASI PERATURAN GUBERNUR JAWA TENGAH NOMOR 22 TAHUN 2019 TENTANG PENERIMAAN PESERTA DIDIK BARU PADA SEKOLAH MENENGAH ATAS (STUDI KASUS DI SMA NEGERI 1 SUKODONO KABUPATEN SRAGEN) - Sutrisno . (JI@P, 2022)
The selection of new students at SMA Negeri 1 Sukodono went smoothly inaccordance with the regulations, applying the zoning route, achievement andshifting the duties of parents/guardians. The purpose of this research is to know theimplementation of Central Java Governor Regulation No. 22 of 2019. The researchmethod is descriptive qualitative, interview and documentation. Determination ofpurposive sampling informants: principals, head of PPDB and guardians ofstudents. Qualitative data analysis includes interview transcripts, data reduction,analysis, interpretation and triangulation. Research results 1) Resources aresufficient to support activities. 2) The disposition of the implementor is very goodin terms of commitment and attitude. 3) Social media socialization communicationhas not been maximized. 4) The bureaucratic structure is quite good in the divisionof committee work. The implementation of the new student admissions policy atSMA Negeri 1 Sukdono has gone well: resources, disposition, communication andbureaucratic structure.Keyword: Implementation; Regulation Of The Governor Of Central JavaNumber 22 Year 2019